(untitled) (Research, Society and Development, 2020)
This work aimed to propose the construction of two clothing products with ergonomic characteristics, to be seen: a men’s T-shirt and a women’s dress. The study is characterized by exploratory research, in which it addressed the needs of the elderly to clothing and their body-movement interaction. Initially, we sought to empathically understand through the visual analysis of clothing products for the elderly, in addition to an exploratory bibliographic review to understand the state of the art of the subject. The methodology used started from the knowledge provided by Bernard Lobach and Mike Baxter, in their product development proposals. As a result, a common denominator that could be explored was reached: the collar. Thus, it focused on the development of a collar that does not hurt them and at the same time provides independence in the motor act of dressing and undressing when using clothing products. To make the practical collar, the raw materials were used 100% cotton and viscolycra, justified by their composition properties. The proposal of the project is, therefore, to provide consumers of third parties with a product that offers, practically and intelligently, a viable solution that gives autonomy to the experience of the elderly, to the extent that it is also able to facilitate the work actions of their caregiver.